PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP CUSTOMER TRUST DAN CUSTOMER LOYALTY PADA BANK BRI CABANG PEKANBARU IMAM MUNANDAR. - Febriyan, Harry; Sulistyowati, Lilis (Jurnal Tepak Manajemen Bisnis, 2014)
This study aimed to analyze the influence of Customer Relationship Management (CRM) to the Customer rTust and Customer Loyalty at Bank BRI Branch pekanbaru Imam Munandar . Quantitative r esearch was conducted on a population of customer deposits with a total sample of 150 customers, Savings, deposits and current accounts using proportional stratified random sampling method. Data collection techniques used in this study is a survey and observation using data analysis techniques Path Analysis with SPSS. The results showed that all dimensions of CRM: People, Process, and Technology in partial significant effect on Customer T rust. Customer Trusth as a significant influence on Customer Loyalty. While theoverall CRM significant effect on Customer Loyalty.Keywords: Customer Relationship Management (CRM), CustomerT rust,Customer Loyalty.